Boosting Vaccine-Elicited Respiratory Mucosal and Systemic COVID-19 Immunity in Mice With the Oral Lactobacillus plantarum - Xu, Jianqing; Ren, Zhihong; Cao, Kangli; Li, Xianping; Yang, Jing; Luo, Xuelian; Zhu, Lingyan; Wang, Xiangwei; Ding, Longfei; Liang, Junrong; Jin, Dong; Yuan, Tingting; et al. (Frontiers in Nutrition, 2021)
Boosting and prolonging SARS-CoV-2 vaccine-elicited immunity is paramount for containing the COVID-19 pandemic, which wanes substantially within months after vaccination. Here we demonstrate that the unique strain of probiotic Lactobacillus plantarum GUANKE (LPG) could promote SARS-CoV-2-specific immune responses in both effective and memory phases through enhancing interferon signaling and suppressing apoptotic and inflammatory pathways. Interestingly, oral LPG administration promoted SARS-CoV-2 neutralization antibodies even 6 months after immunization. Furthermore, when LPG was given immediately after SARS-CoV-2 vaccine inoculation, specific neutralization antibodies could be boosted >8-fold in bronchoalveolar lavage (BAL) and >2-fold in sera, T-cell responses were persistent and stable for a prolonged period both in BAL and the spleen. Transcriptional analyses showed that oral application of LPG mobilized immune responses in the mucosal and systemic compartments; in particular, gut-spleen and gut-lung immune axes were observed. These results suggest that LPG could be applied in combination with SARS-CoV-2 vaccines to boost and prolong both the effective and memory immune responses in mucosal and systemic compartments, thereby improving the efficacy of SARS-CoV-2 vaccination.